2022 American College of Rheumatology/American Association of Hip and Knee Surgeons Guideline for the Perioperative Management of Antirheumatic Medication in Patients With Rheumatic Diseases Undergoing Elective Total Hip or Total Knee Arthroplasty. Issue 9 (20th June 2022) - Goodman, Susan M.; Springer, Bryan D.; Chen, Antonia F.; Davis, Marshall; Fernandez, David R.; Figgie, Mark; Finlayson, Heather; George, Michael D.; Giles, Jon T.; Gililland, Jeremy; Klatt, Brian; MacKenzie, Ronald; et al.
Abstract : Objective: To develop updated guidelines for the perioperative management of disease‐modifying medications for patients with rheumatic diseases, specifically those with inflammatory arthritis (IA) and those with systemic lupus erythematosus (SLE), undergoing elective total hip arthroplasty (THA) or elective total knee arthroplasty (TKA). Methods: We convened a panel of rheumatologists, orthopedic surgeons, and infectious disease specialists, updated the systematic literature review, and included currently available medications for the clinically relevant population, intervention, comparator, and outcomes (PICO) questions. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology to rate the quality of evidence and the strength of recommendations using a group consensus process. Results: This guideline updates the 2017 recommendations for perioperative use of disease‐modifying antirheumatic therapy, including traditional disease‐modifying antirheumatic drugs, biologic agents, targeted synthetic small‐molecule drugs, and glucocorticoids used for adults with rheumatic diseases, specifically for the treatment of patients with IA, including rheumatoid arthritis and spondyloarthritis, those with juvenile idiopathic arthritis, or those with SLE who are undergoing elective THA or TKA. It updates recommendations regarding when to continue, when to withhold, and when to restart these medications and the optimal perioperative dosing of glucocorticoids. Conclusion: This updated guideline includes recently introduced immunosuppressive medications to help decision‐making by clinicians and patients regarding perioperative disease‐modifying medication management for patients with IA and SLE at the time of elective THA or TKA.